How Big Data Shapes New Consumption: Mechanisms and Impacts - Lang, Pengwu (Journal of Global Economy, Business and Finance, 2026)
The 2025 Government Work Report highlighted the imperative to "accelerate the development of digital, green, and intelligent new consumption." This study constructs an index system for new consumption and utilizes the national big data comprehensive pilot zone policy as a quasi-natural experiment, applying the Difference-in-Differences (DID) method to empirically assess big data's impact on new consumption development. Results reveal that the policy significantly fosters new consumption growth, expands consumption areas, and optimizes consumption models, with long-term positive effects. The policy's promotion effect is more pronounced in eastern regions, municipal districts, and medium to large cities. Mechanism analysis identifies human capital accumulation, innovation stimulation, and information asymmetry reduction as key drivers. Consequently, we recommend big data application, strengthening digital talent cultivation, expanding technological spillovers, and implementing differentiated development strategies to promote new consumption.